Effectiveness of bioagents and neem formulations against Fusarium wilt of carnation - MANICA TOMAR*, SUNITA CHANDEL and (Indian Phytopathology, 2008)
A study was conducted for two consecutive years i.e. 2005 and 2006 to gauge the effect of biocontrol agents and neem based formulations on wilt of carnation. Out of the neem formulations used, Achook was found to be most effective in managing the disease with 89.63% disease control followed by Neemazal. While amongst the BCAs, T. harzianum was found to be superior over T. viride and Gliocladium virens in managing the disease. Under field conditions all the treatments had a positive effect on the plant growth parameters.